(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
One definition of a tax is a levy levied against citizens or owners of property in order to raisefunds for public services. Therefore, tax is not a voluntary payment or donation that one chooses on theirown but rather a required contribution. It’s money that the lawmaker is required to collect. Taxes can beimposed either directly or indirectly. Effective tax system and procedures can lead to revenue growth thatis perhaps a little quicker than GDP (Gross Domestic Product). The collection and distribution of taxrevenue is the focus of tax law. There are several origins for tax regulations. They have their origins infederal and state constitutions, statutes, and ordinances. The practice of tax law includes learning about,enforcing, and defending the payment or nonpayment of taxes. In this Article the author has explainedthe Constitutional provisions in a very simple manner so that the layman can also understand thecomplicated provisions related to different types of Taxes.